Alzheimer's Disease: Exploring the Role of Inflammation and Implications for Treatment. (17th November 2015) - McCaulley, Mark E.; Grush, Kira A.
Abstract : Alzheimer's disease (AD) is a neurodegenerative disorder characterized by both structural abnormalities and inflammation in the brain. While recent research has chiefly focused on the structural changes involved in AD, understanding the pathophysiology and associated inflammation of the AD brain helps to elucidate potential therapeutic and preventative options. By exploring the data supporting an inflammatory etiology of AD, we present a case for the use of existing evidence-based treatments addressing inflammation as promising options for treating and preventing AD. We present data demonstrating tumor necrosis factor alpha association with the inflammation of AD. We also discuss data supporting TNF alpha associated inflammation in traumatic brain injury, stroke, and spinal disc associated radiculopathy. We augment this previously unarticulated concept of a unifying pathophysiology of central nervous system disease, with reports of benefits of TNF alpha inhibition in many hundreds of patients with those diseases, including AD. We also assess the pathophysiologic and clinical trial evidence supporting the role of other inflammation resolving treatments in AD. In aggregate, the data from the several potentially effective therapeutic and preventative options contained within this report presents a clearer picture of next steps needed in research of treatment alternatives.